Pentahelix's function in developing tourist areas in Negeri Liang, Salahutu District - Talakua, Jeane; Mike J Rolobessy (PT FORMOSA CENDEKIA GLOBAL, 2024)
Efforts to develop tourism in Maluku by implementing the Pentahelix Concept are one of the offers from the Ministry of Tourism related to tourism development in an area. However, the application of the pentahelix concept is not yet fully optimal in strategic tourist areas such as Liang Country. The important role of all stakeholders in tourism development. These parties are the regional government, Liang state government, business actors, and the community/society plus the media. These parties constitute a unit that is complementary and interrelated. The pentahelix model seeks to encourage the tourism sector and the tourism system by increasing roles in creating economic benefits that can be taken from tourism activities in Liang Country, thereby creating a wide multiplier effect for the people of Liang Country